The basics of genetics - O'Daly, Anne, 1966- (Core concepts (Rosen Publishing Group), 2023)
Introduces the fundamentals of genetics, discussing the principles of inheritance, cell division, DNA and RNA, genomes, and human genetics concepts. Also includes a biography of scientist Gregor Mendel. Features full-color illustrations, informative sidebars, a timeline, a glossary, and further resources.